Above cuff vocalisation (ACV): A scoping review. Issue 1 (1st November 2020) - Petosic, Antonija; Viravong, Marit F.; Martin, Anna M.; Nilsen, Cecilie B.; Olafsen, Kjell; Berntzen, Helene
Abstract: Introduction: Patients in intensive care frequently suffer from not being able to communicate verbally. The aim of this scoping review was to study the safety and effectiveness of the above cuff vocalisation (ACV) on speech and quality of life (QOL) in patients dependent on a cuffed tracheostomy. Methods: A scoping review was conducted. The databases Ovid Medline, Cochrane Library, and Embase were systematically searched in May 2020. We included clinical studies with patients exposed to ACV where speech, QOL or safety issues were assessed. Results: Overall, 17 studies were included, of which 15 were observational and 2 were randomised controlled trials. Totally, 231 patients were included. ACV enabled most of the included patients (115/131; 88%) to speak with an audible voice or whisper (moderate quality of evidence). Voice related QOL (V‐RQOL) and QOL in mechanically ventilated patients (QOL‐MV) improved from pre‐ to post‐ ACV compared to a control group not tolerating a one‐way speaking valve ( P = .01 and P = .04, respectively) (very low quality of evidence). Several minor complications or problems were reported in 20/75 (27%) cases in addition to two serious adverse events: subcutaneous emphysema in one patient where the tracheostomy was dislodged and a distended trachea in another due to the misconnection of continuous gas to the cuff (low/ very low quality of evidence). Conclusion: ACV facilitated communication in patients dependent on a cuffed tracheostomy and attempting to communicate. Quality of evidence in improved V‐RQOL and QOL‐MV was very low. Several minor complications and two serious adverse events were reported.